Business Performance under Green Accounting and Technofinance: The Role of Regulatory Support - Restu Alpiansah; Nur Fitriyah; Mariusz Lewandowski; Katarzyna Liczmańska Kopcewicz (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2026)
Main Purpose – This study aims to examine the impact of Green Accounting and Technofinance on the Business Performance on MSMEs in Lombok, West Nusa Tenggara with the Regulatory Support serving as the moderating variable. Method – This research utilises a quantitative methodology, employing survey data gathered from 120 MSMEs in Lombok. The data were analysed using Partial Least Squares Structural Equation Modelling (SEM – PLS). Main Findings – The result indicates that Green Accounting and Technofinance have a beneficial impact on Business Performance, however the regulatory Support fails to enhance Green Accounting and adversely moderates the advantages of Technofinance. Theory and Practical Implications – The results indicate that internal managerial practices are more pivotal than regulatory variable in enhancing MSME performance. Policymakers are urged to streamline regulatory frameworks, while MSMEs should emphasise sustainable practices and financial digitalisation to improve competitiveness. Novelty – This research article offers novel empirical data about the dual moderating function of regulatory support and the relationship among sustainability practices, financial technology and MSMEs performance.